Close knit ebook A novel. - Colgan, Jenny (Mure, 2024)
Follow Gertie MacIntyre from knitting circle to air stewardess in this glorious and romantic summer novel set in Scotland's windswept Northern isles, by beloved New York Times bestselling author Jenny Colgan. In the northernmost reaches of Scotland, where a string of little islands in the North Sea stretches towards Norway, lives Gertie MacIntyre, a proud island girl by birth. Her social circle is small but tight: family and friends, particularly the women in her knitting circle. In the whitewashed cottages of their hometown, everyone knows everyone, and the ladies of the knitting circle know more than most. In a place of long dark winters and geographic isolation, the knitting circle is a precious source of gossip, home, laughter, and comfort for them all. And while she knits, Gertie's busily plotting what to do with the rest of her life. When Gertie develops a crush on Callum Frost, who owns the local airline, she dares herself to take a job as an air stewardess on the little plane that serves the local islands. Terrifying at first, the sixteen-seat puddle jumper also offers the first taste of real freedom she's ever known. Will Gertie's future lie in the skies? Or will she need to go further afield to find the adventure she craves?